Pembuatan Sabun Biji Alpukat Sebagai Solusi Ramah Lingkungan Dan Pemberdayaan Ekonomi Masyarakat Di Kalurahan Sumberwungu, Gunung Kidul, Yogyakarta - Larasati, Dwi; Rahayu, Budi; Viyani, Ari Okta; Sunarsih, Tri; Sarmin, Sarmin; Airin, Claude Mona; Soffan, Alan; Astuti, Endah Puji; Shanti, Elvika Fit Ari (PPPM POLTESA, 2024)
Avocado seeds, often regarded as waste, have significant potential as an alternative raw material for producing environmentally friendly products, such as natural soap. These seeds contain beneficial active compounds, including antioxidants, unsaturated fatty acids, and vitamin E, which contribute to skin health. This community service program aims to train the residents of Sumberwungu Village, Gunung Kidul, Yogyakarta, in making soap using avocado seeds as the primary ingredient through the cold process method. The program’s objectives are not only to reduce waste but also to enhance the community's skills in producing high-quality soap that can be marketed as a local product with economic value. It is hoped that through this training, participants will be able to utilize avocado seeds to create soap with skin benefits, opening new economic opportunities for small businesses. The results of the community service activities indicated that the participants welcomed the initiative enthusiastically and actively engaged in the training process. Evaluations revealed a significant improvement in participants’ pretest and posttest scores, demonstrating a better understanding of the soap-making process and its applications. Furthermore, participants were directly involved in soap production using an effective cold saponification technique. This avocado seed soap shows promising market potential. Overall, the program not only offers economic benefits but also raises public awareness of the importance of waste management and environmental sustainability.